Circadian clock gene NPAS2 promotes reprogramming of glucose metabolism in hepatocellular carcinoma cells. (28th January 2020) - Yuan, Peng; Yang, Tao; Mu, Jiao; Zhao, Jing; Yang, Yi; Yan, Zhaoyong; Hou, Yiran; Chen, Cheng; Xing, Jinliang; Zhang, Hongxin; Li, Jibin
Abstract: Emerging evidences show that dysregulation of circadian genes is closely associated with tumorigenesis. However, whether circadian genes regulate the reprogramming of metabolism in tumor cells is largely unknown. Here, we showed that NPAS2, one of the core circadian molecules, significantly contributed to the reprogramming of glucose metabolism mainly through two mechanisms. On the one hand, NPAS2 upregulated the expression of glycolytic genes GLUT1, HK2, GPI, ALDOA, ENO2, PKM2 and MCT4 . On the other hand, NPAS2 downregulated the expression of peroxisome proliferator-activated receptor gamma coactivator 1 alpha (PGC-1α). Mechanistically, HIF-1α was found to be a direct transcriptional target of NPAS2, which mediated both the upregulation of glycolytic genes and downregulation of mitochondrial biogenesis in HCC cells. In addition, we found that upregulation of NPAS2 expression was mainly due to the downregulation of miR-199b-5p. In vitro and in vivo assays further indicated that HIF-1α-mediated reprogramming of glucose metabolism played a critical role in NPAS2-regulated growth and metastasis of HCC cells. Our findings demonstrate that NPAS2 plays a critical role in glucose metabolism reprogramming, suggesting that NPAS2 may serve as a potential therapeutic target in HCC. Highlights: NPAS2 significantly enhanced the Warburg effect of HCC cells. HIF-1α was essential for the effect of NPAS2 in glucose metabolism reprogramming. NPAS2 transcriptionally up-regulated HIF-1α expression in HCC cells. Downregulation of miR-199b-5p was involved in overexpression of NPAS2 in HCC cells.